JQ1 as a BRD4 Inhibitor Blocks Inflammatory Pyroptosis-Related Acute Colon Injury Induced by LPS - Chen, Ling; Zhong, Xiaolin; Cao, Wenyu; Mao, Mingli; Li, Wei; Yang, Hui; Li, Menglin; Shi, Mengmeng; Zhang, Yuan; Deng, Yincheng; Zu, Xuyu; Liu, Jianghua (Frontiers in Immunology, 2021)
Endotoxemia is a severe inflammation response induced by infection especially bacterial endotoxin translocation, which severely increases mortality in combination with acute colon injury. Bromodomain-containing protein 4 (BRD4) is an important Bromo and Extra-Terminal (BET) protein to participate in inflammatory responses. However, it is still unknown about the specific connection between BRD4 and inflammation-related pyroptosis in endotoxemia colon. Here, through evaluating the mucous morphology and the expression of tight junction proteins such as occludin and ZO1, we found the upregulation of BRD4 in damaged colon with poor tight junction in an endotoxemia mouse model induced by lipopolysaccharides (LPS). Firstly, the BRD4 inhibitor JQ1 was used to effectively protect colon tight junction in endotoxemia. As detected, high levels of pro-inflammation cytokines IL6, IL1β and IL18 in endotoxemia colon were reversed by JQ1 pretreatment. In addition, JQ1 injection reduced endotoxemia-induced elevation of the phosphorylated NF κB and NLRP3/ASC/caspase 1 inflammasome complex in colon injury. Furthermore, activated pyroptosis markers gasdermins in endotoxemia colon were also blocked by JQ1 pretreatment. Together, our data indicate that BRD4 plays a critical role in regulating pyroptosis-related colon injury induced by LPS, and JQ1 as a BRD4 inhibitors can effectively protect colon from endotoxemia-induced inflammation injury.